Heat Transfer During Subcooled Boiling in Tubes (A Review) - Gakal, P.G.; Gorbenko, G.A.; Turna, R.Yu.; Reshitov, E.R. (Проблеми машинобудування, 2019)
This article provides a review of the correlations and models for determining the intensity of heat transfer during subcooled boiling in pipes. These advantages and disadvantages were determined both by analyzing the physical laws of subcooled boiling and by comparing the results that were obtained by the authors of this article by means of various models of subcooled boiling with the experimental data obtained during the study of heat transfer during the subcooled boiling of ammonia in a cylindrical heated tube. As a result of the review and comparison with the experimental data, it was determined that the existing correlations and models describe the subcooled boiling of ammonia with insufficient accuracy, especially in the area of the combined effect of forced convection and nucleate boiling. В статті наведено огляд кореляцій та моделей для визначення інтенсивності теплообміну під час недогрітого кипіння теплоносія у трубах. В статті виконано аналіз переваг та недоліків кореляцій та моделей. В результаті огляду та порівняння з експериментальними даними визначено, що існуючі кореляції та моделі описують недогріте кипіння аміаку з недостатньою точністю, особливо у разі спільного впливу вимушеної конвекції та пузиркового кипіння. В статье представлен обзор корреляций и моделей для определения интенсивности теплообмена при недогретом кипении в трубах. В статье проведен анализ достоинств и недостатков корреляций и моделей. В результате обзора и сравнения с экспериментальными данными определено, что существующие корреляции и модели описывают недогретое кипение аммиака с недостаточной точностью, особенно при совместном влиянии вынужденной конвекции и пузырькового кипения.